Emerging Infections Due to Shewanella spp.: A Case Series of 128 Cases Over 10 Years - Ng, Wincy Wing-Sze; Shum, Hoi-Ping; To, Kelvin Kai-Wang; Sridhar, Siddharth (Frontiers in Medicine, 2022)
Background Shewanella species are emerging pathogens that can cause severe hepatobiliary, skin and soft tissue, gastrointestinal, respiratory infections, and bacteremia. Here we reported the largest case series of infections caused by Shewanella species. Aim To identify the clinical features and risk factors predisposing to Shewanella infections. To evaluate resistance pattern of Shewanella species and appropriateness of antibiotic use in the study cohort. Methods Patients admitted to a regional hospital in Hong Kong with Shewanella species infection from April 1, 2010 to December 31, 2020 were included. Demographics, antibiotics, microbiology, and outcomes were retrospectively analyzed. Findings Over the 10 years, we identified 128 patients with Shewanella species infection. 61.7% were male with a median age of 78 (IQR 65–87). Important underlying diseases included hepatobiliary diseases (63.3%), malignancy (26.6%), chronic kidney disease or end-stage renal failure (25.8%), and diabetes mellitus (22.7%). Hepatobiliary infections (60.4%) were the most common clinical manifestation. Majority (92.2%) were infected with Shewanella algae, while 7.8% were infected with Shewanella putrefaciens. The identified organisms were usually susceptible to ceftazidime (98.7%), gentamicin (97.4%), cefoperazone-sulbactam (93.5%) and ciprofloxacin (90.3%). Imipenem-susceptible strains were only present in 76.6% of isolates. Conclusion This largest case series suggested that Shewanella infections are commonly associated with underlying comorbidities, especially with hepatobiliary diseases and malignancy. Although Shewanella species remained largely susceptible to third and fourth generation cephalosporins and aminoglycosides, carbapenem resistance has been on a significant rise.